PENGEMBANGAN PENDIDIKAN AGAMA ISLAM - Susanti, Desi (Islamic Faculty of Nurul Jadid, 2017)
This research of background overshadow by existence of strategic role which owned activity of tutorial Education of Islamic Religion to be developed as one of strategy study of PAI. On the other side existence of phenomenon education of religion which not yet optimal and not yet touched domain truthfully effect of limitation of meeting. Target of this research to formulate congeniality of Education of Islamic Religion and also how development, strategy and challenge Development of Islamic Religion.